Kesantunan Berbahasa Siswa dengan Guru Bahasa Indonesia melalui Media Sosial WhatsApp di SMP Negeri 2 Bukittinggi - Marlen, Lili; Atmazaki, Atmazaki (Universitas Negeri Padang, 2020)
ABSTRACTÂ This article explains the language politeness of students with Indonesian language teachers through WhtasApp social media at SMP Negeri 2 Bukittinggi. There are four objectives of the research. First, describe the communication ethics of students with Indonesian language teachers through WhatsApp social media at SMP Negeri 2 Bukittinggi. The second describes the principle of politeness according to Leech, students and Indonesian language teachers through WhatsApp social media at SMP Negeri 2 Bukittinggi. The third describes the language politeness scale according to Leech students and Indonesian language teachers through WhatsApp social media at SMP Negeri 2 Bukittinggi. The fourth describes the language politeness of students with Indonesian language teachers through WhatsApp social media at SMP Negeri 2 Bukittinggi. This research is a qualitative research using descriptive method. The data in this study were junior high school students' speech to the teacher via WhatsApp social media. Researchers took data from thirty students consisting of grade 7, grade, and grade 9. Data was collected by asking directly to the data source and completed by interviewing Indonesian language teachers to strengthen the data. There are four research results. First, from the 35 existing data, it was found that 31 data had good ethics. Second, students generally have applied the principle of politeness according to Leech. Third, students generally apply the politeness scale in language. Fourth, from 35 data on WhatsApp messages between students and Indonesian language teachers, 25 polite data were found.Â Kata kunci: Kesantunan, etika, maksim sopan santun, skala pragmatik, WhatsAppÂ